Obedience Will Result to Holiness and Restored Relationship With God According To Leviticus 5:14-19 And Implications For Christian Education - Nababan, Andrianus; Salucan, Darwin (the International Journal of Education, Theology, and Humanities, 2024)
The purpose of this article is to discuss the concept of obedience in bringing about holiness and restoring relationship with God as taught in Leviticus 5:14-19 and its implications for Christian education. In Leviticus 5:14-19, there is a provision for guilt offerings that shows the importance of people's obedience in following God's rules as a form of repentance and respect for His holiness. Through sincere obedience and repentance, believers are restored in their relationship with God and return to a state of holiness before Him. In the context of Christian education, this principle can be applied to the development of students' character, where education focuses not only on academic knowledge but also on spiritual and moral formation. Learning about obedience and holiness emphasizes the importance of living a life of integrity, responsibility, and strengthening one's relationship with God. Christian education that integrates the theological understanding of Leviticus 5:14-19 can encourage learners to understand the importance of obedience as a path to holiness and to improve their relationship with God, and make it the basis for developing personal character based on Christian values.